Tolerance of MRSA ST239-TW to chlorhexidine-based decolonization: Evidence for keratinocyte invasion as a mechanism of biocide evasion. Issue 2 (February 2019) - Marbach, Helene; Vizcay-Barrena, Gema; Memarzadeh, Kaveh; Otter, Jonathan A.; Pathak, Smriti; Allaker, Robert P.; Harvey, Richard D.; Edgeworth, Jonathan D.
Highlights: MRSA clones with a low chlorhexidine MIC phenotype can still survive decolonization regimes. in vivo decolonization tolerance of ST239-TW may not be due to the presence of qacA alone. Elevated fibrinogen and fibronectin binding by ST239-TW is indicative of increased cell uptake. ST239-TW shows increased chlorhexidine survival when adhered and internalized to keratinocytes. Summary: Objectives: Information on genetic determinants of chlorhexidine tolerance ( qacA carriage and MIC) in vitro is available, although evidence of the clinical impact and mechanisms remain poorly understood. We investigated why, following chlorhexidine intervention, prevalent epidemic MRSA ST22 and ST36 clones declined at an ICU, whilst an ST239-TW clone did not. The chlorhexidine tolerant ST239-TW phenotypes were assessed for their protein binding, cell adhesion and intracellular uptake potential. Methods: Six ST22, ST36 and ST239-TW bloodstream infection isolates with comparable chlorhexidine MICs were selected from a 2-year outbreak in an ICU at Guy's and St. Thomas' Hospital. Isolates were tested for fibrinogen and fibronectin binding, and adhesion/internalization into human keratinocytes with and without biocide. Results: Binding to fibrinogen and fibronectin, adhesion and intracellular uptake within keratinocytes ( P  < 0.001) and intracellular survival in keratinocytes under chlorhexidine pressure (ST22 3.18%, ST36 4.57% vs ST239-TW 12.79%; P  < 0.0001) was consistently higher for ST239-TW. Conclusions: We present evidence that MRSA clones with similarly low in vitro tolerance to chlorhexidine exhibit different in vivo susceptibilities. The phenomenon of S. aureus adhesion and intracellular uptake into keratinocytes could therefore be regarded as an additional mechanism of chlorhexidine tolerance, enabling MRSA to evade infection control measures.